A study into the distribution network of print media in Singapore. - Lum, Selina Wei Ling. (2009)
This study looks into the distribution process of print media in Singapore. An exploratory approach was undertaken to document the development of the distribution network of newspaper vendors and observe the distribution flow of newspapers and magazines from the printing plants to households and news-stands. The findings reveal the existence of an intricate and established distribution network comprising distributors, newsvendors, as well as sales outlets. This network had its beginnings in the late 1960s and early 1970s, a period when secret societies were prevalent and influenced the system. The newsvendor network has since evolved from an independent network to one that is partially controlled by major distributors. It was also found that there are other distributors who form alternative distribution systems to deliver publications to local retail outlets as well as for export. The phasing out of makeshift stalls prompted both newsvendors and distributors to come up with other alternatives such as vending machines and distributor-owned kiosks.